Performance of kids of Rohilkhandi under different weaning systems - RANGASWAMY, R; PATEL, B H M; UPADHYAY, D; SAHU, S; TOMAR, A K S; GAUR, G K; DUTT, T; VERMA, M R; BHUSAN, B (The Indian Journal of Animal Sciences, 2015)
The study was conducted at Sheep and Goat farm, Livestock Production and Management section, IVRI, Izatnagar. Kids (30) obtained from 23 dams were allocated to 3 treatment groups viz. Gr1: Traditional weaning (kids remained with dam for 3 months and subsequently weaned), Gr2: Partial weaning (kids remained with dam for 1 month, during second month, kids were separated from the dam during day hours but had eye contact and merged with dam in the night further kids were weaned at 60 days), and Gr3: Early weaning (kids remained with dam for 2 months and subsequently weaned). Body weight and measurements were taken every fortnight. Fortnight body weight gain and ADG was also calculated. The daily intake of hay (wheat straw), green fodder (maize/ berseem) and concentrate were recorded. The overall FCR was calculated by dividing average total weight gain from total average dry matter intake. The final body weight in Gr3 was higher than other 2 groups (Gr1 and Gr2) however, the mean body weights were nonsignificant from each other. The total body weight gain (kg) was higher in Gr3 than Gr2, however it was not significantly different from Gr1. The ADG in Gr1, Gr2 and Gr3 were 14g, 21g and 21g, respectively, and values were comparable among the groups. All body measurement CG, HG and PG did not differ significantly between groups. However, BL after fourth fortnight onwards was significantly lower in Gr1 than Gr2 and Gr3. The overall fortnight total DM intake in Gr1, Gr2 and Gr3 were 2.21±0.20, 2.2±0.20 and 2.09±0.28 kg respectively. The overall FCR was 1: 10, 1: 8.1 and 1: 7.5 in Gr1, Gr2 and Gr3. It can be concluded that either partial or early weaning could be adopted at the farm level.